Applying Active Teaching Methods in Teaching for Students of Vietnamese studies in the Department of Linguistics and Literature of Ho Chi Minh City University of Education - Ngoc, Nguyen Anh (International Journal of Humanities and Education Development (IJHED), 2022)
The Vietnamese studies major at the Department of Linguistics and Literature, Ho Chi Minh City University of Educationis a Scientology. Thisologyprovides basic, systematic, modern, and practical knowledge about Vietnamese studies…. especially about Vietnam tourism. The training of Vietnamese studies always strives to achieve positive effects to meet the needs of learners and the demand for human resources in society. To achieve these, lecturers have applied active teaching methods in teaching. Visualization, project teaching, and experiential teaching... are typical active teaching methods applied in teaching students of Vietnamese studies at the Department of Linguistics and Literature, Ho Chi Minh City University of Education now. The application of these methods received positive feedback from both lecturers and students. Lecturers are always encouraged to apply active teaching methods in teaching to both improve training quality and increase students' interest and capacity